2021
DOI: 10.3390/life11090951
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Activity and Function of the Protein Arginine Methyltransferase 6

Abstract: Members of the protein arginine methyltransferase (PRMT) family methylate the arginine residue(s) of several proteins and regulate a broad spectrum of cellular functions. Protein arginine methyltransferase 6 (PRMT6) is a type I PRMT that asymmetrically dimethylates the arginine residues of numerous substrate proteins. PRMT6 introduces asymmetric dimethylation modification in the histone 3 at arginine 2 (H3R2me2a) and facilitates epigenetic regulation of global gene expression. In addition to histones, PRMT6 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 195 publications
(305 reference statements)
0
19
0
Order By: Relevance
“…PRMT6, a type I PRMT, di-methylates the arginine residues of both histones and non-histones asymmetrically [16]. Numerous pieces of evidence suggest that PRMT6 is involved in a variety of cellular functions, including cellular division, RNA metabolism, cellular senescence, and cellular homeostasis [17]. Now, it is widely reported that PRMT6 acts as a tumor mediator and exerts a dual role in human cancer.…”
Section: Introductionmentioning
confidence: 99%
“…PRMT6, a type I PRMT, di-methylates the arginine residues of both histones and non-histones asymmetrically [16]. Numerous pieces of evidence suggest that PRMT6 is involved in a variety of cellular functions, including cellular division, RNA metabolism, cellular senescence, and cellular homeostasis [17]. Now, it is widely reported that PRMT6 acts as a tumor mediator and exerts a dual role in human cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence indicates that other PTMs, particularly methylation and the adding of poly (ADP-ribose) (PAR) chains (PARylation), influence FOXO3a activity. In mice, the stimulation of PRMT6 (protein arginine methyltransferase 6) has been found to promote the methylation of FOXO3a at Arg188 and Arg249, resulting in enhanced autophagy activity [ 77 , 78 ]. On the other hand, the PTM regulated by poly (ADP-ribose) polymerase-1 (PARP1) may be triggered by ROS and is implicated in the control of FOXO3a activity.…”
Section: Regulation Of Foxo3a Upon Oxidative Stressmentioning
confidence: 99%
“…PRMT6, a type I PRMT, dimethylates the arginine residues of both histones and non-histones asymmetrically [16]. Numerous pieces of evidence suggest that PRMT6 is involved in a variety of cellular functions, including cellular division, RNA metabolism, cellular senescence, and cellular homeostasis [17]. Now, it is widely reported that PRMT6 acts as a tumor mediator and exerts a dual role in human cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Now, it is widely reported that PRMT6 acts as a tumor mediator and exerts a dual role in human cancer. In hepatocellular carcinoma, there is a signi cant correlation between decreased PRMT6 expression and short overall survival, whereas PRMT6 overexpression is associated with tumorigenicity and invasiveness in gastric cancer and lung cancer [17,18]. It has been described as an arginine methyltransferase that methylates CRAF, P16, and BAG5 proteins involved in tumor progression [19][20][21].…”
Section: Introductionmentioning
confidence: 99%